Dinamika Wahabisme di Lombok Timur: Problem Identitas, Kesalehan dan Kebangsaan - Said, Mohammad (FIKRAH, 2019)
This paper will examine the influence of Wahabism on local religious culture and practice of ‎the NU and NW. Second, ‎the way Wahabist prcatice da’wa in East Lombok. Third the Wahabi’s views of democracy and nationalism. The presence of Wahabi ideology successfully eliminates culturally religious practices of the NU model. This Arabization further leads to problems of marginalization of both ethnicity and Sasakness identity that eventually bear symptoms of “cultural otherness”. The wahabism development could not be separated from a large funds from Saudi Arabia which mostly used to build mosques and Islamic schools, radio, Youtube channel, and local television as da’wah media. This foreign abundant flow of aid contributes to waning nationalism of this community as they consider the State to have been absent in facilitating their civil rights. As a consequence, this community bans any form of respect to the State, including flag ceremony and national anthems.